2009
DOI: 10.1016/j.cyto.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

TNFR and LTβR agonists induce follicle-associated epithelium and M cell specific genes in rat and human intestinal epithelial cells

Abstract: M cells assist mucosal immune surveillance by transcytosis of particles to underlying lymphoid tissue, but the mechanisms of M cell differentiation are poorly understood. To develop a better defined cell culture model of M cell differentiation, we treated human (Caco-2BBe) and rat (IEC-6) intestinal epithelial cell lines with lymphotoxin beta receptor (LTβR) and TNF receptor (TNFR) agonists. Treated cells were studied for regulation of genes associated with M cell and FollicleAssociated Epithelium (FAE). We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 43 publications
4
49
0
Order By: Relevance
“…A function for 4-1BB at earlier thymic differentiation stages has not been reported; however, some studies have shown that 4-1BB can regulate TNF-a expression (46,47) and vice versa (48), suggesting a possible link between the two. Overexpression of TNF-a under control of its natural promoter has been reported to block early thymocyte development at the DN1 to DN2 stage, promoting accelerated thymic atrophy (49) and mirroring our own observations in the NOD thymus.…”
Section: Discussionmentioning
confidence: 98%
“…A function for 4-1BB at earlier thymic differentiation stages has not been reported; however, some studies have shown that 4-1BB can regulate TNF-a expression (46,47) and vice versa (48), suggesting a possible link between the two. Overexpression of TNF-a under control of its natural promoter has been reported to block early thymocyte development at the DN1 to DN2 stage, promoting accelerated thymic atrophy (49) and mirroring our own observations in the NOD thymus.…”
Section: Discussionmentioning
confidence: 98%
“…Human glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as a reference gene for all quantitative PCRs (qPCRs). Primers used in qPCR assays were described previously (16). The comparative ⌬⌬C T method was used to determine the relative amount of gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in a broader context, inflammatory processes may also disrupt microvillus formation and the maintenance of the electrostatic barrier even in the absence of effacement effectors and TTSSs. For example, inflammatory cytokines such as lymphotoxin and tumor necrosis factor alpha (TNF-␣) were found to reduce microvillus formation in Caco2BBe cells in vitro (16); since these cytokines are known effectors in inflammatory bowel disease (39,40), a similar effect on microvilli in vivo may be relevant to mucosal barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And HIEC may have a number of different applications (36). For example, they can be used to evaluate the effects of growth or maturation factors on the expression of membrane receptors and antigens, enzymatic activities, transport and secretory functions (37), to study drug metabolism, and to investigate carcinogenic factors and agonists (38).…”
Section: Discussionmentioning
confidence: 99%